1985
DOI: 10.1182/blood.v66.1.120.120
|View full text |Cite
|
Sign up to set email alerts
|

Preleukemic state of adult T cell leukemia: abnormal T lymphocytosis induced by human adult T cell leukemia-lymphoma virus

Abstract: We report the clinical, hematologic, and immunologic features of 18 preleukemic adult T cell leukemia (pre-ATL) cases with abnormal T lymphocytosis induced by human adult T cell leukemia-lymphoma virus (HTLV/ATLV). The patients were from the Nagasaki district, which is one of the most endemic areas of ATL in Japan. Pre-ATL is a subclinical T cell abnormality differing from ATL. It is characterized by an insidious onset and appearance of abnormal T lymphocytes (10% to 40%) in the peripheral blood without clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(18 citation statements)
references
References 17 publications
1
15
0
2
Order By: Relevance
“…In ATL patients with leukaemia, flower cells are usually monoclonally infected with HTLV-I (Kinoshita et al, 1985;Chen et al, 1995). The prevalence of abnormal lymphocytes with flower cell features (at a frequency of 1% or less of white blood cells) in asymptomatic, healthy, HTLV-I-positive Japanese subjects has been reported as high as 43-47% (Kinoshita et al, 1985;Yamaguchi et al, 1988;Tachibana et al, 1992). Tachibana et al (1992) reported a correlation between the presence of flower cells and high proviral load among asymptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In ATL patients with leukaemia, flower cells are usually monoclonally infected with HTLV-I (Kinoshita et al, 1985;Chen et al, 1995). The prevalence of abnormal lymphocytes with flower cell features (at a frequency of 1% or less of white blood cells) in asymptomatic, healthy, HTLV-I-positive Japanese subjects has been reported as high as 43-47% (Kinoshita et al, 1985;Yamaguchi et al, 1988;Tachibana et al, 1992). Tachibana et al (1992) reported a correlation between the presence of flower cells and high proviral load among asymptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The Ably level in peripheral blood smears is used in clinical practice to monitor smoldering ATL for the onset of overt leukemia. In a prospective study of HTLV-I carriers with high levels of Ably and symptoms of immune suppression, 3 of the 18 who were followed developed ATL in 5 years (Kinoshita et al, 1985). In another prospective observation, one of the 14 HTLV-I carriers with variable level of Ably developed ATL after 2 years of follow-up (Yamaguchi et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…These observations have led to the hypothesis that the presence of Ably in HTLV-I carriers with clinical manifestations of immune suppression may predict the subsequent development of ATL. However, it is also known that Ably spontaneously disappears, while monoclonal integration of the provirus in lymphocytes continues (Kinoshita et al, 1985). It is uncertain what Ably represents with regard to pathogenesis, and the validity of low levels of Ably as a marker for the risk of ATL among asymptomatic HTLV-I carriers remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA sequences. HTLV-I has been associated .with a syndrome termed In September 1984, the patient's constitutional symppre-ATL (adult T-cell leukemia/lymphoma) [29], which toms persisted, and he was found to have diffuse lymphis considered to be benign; but based on the monoclo-adenopathy. Six weeks later, nasopharyngeal lymphoid nality of the infected T-cell pclpulation, it might more enlargement and numerous 1-2-cm pulmonary nodules accurately be termed a low-grade malignancy [ 5 ] .…”
Section: Introductionmentioning
confidence: 99%